"I trust HRT, not jamu" : the experience of treating menopausal symptoms among urban Malay women - Mohamad Diah, Nurazzura (2010)
This paper discusses the experience of treating menopausal symptoms among urban Malay working women in Kuala Lumpur. It attempts to demonstrate that HRT has become a preferred treatment by a number of women resulting in a level of medicalisation of the biological process. This is not to say that all, or even most, women use HRT, but rather that the increasing and relatively unquestioned use of HRT indicates a growing acceptance of medicine as an appropriate response to biological change. This study employs ethnographic methods (participation observation and in-depth interviews) with a sample of 30 women aged 48-55. They are formally educated and work in professional paid jobs. Data analysis was performed using the qualitative process. This study shows that treating menopausal symptoms by taking herbal remedies or complying with the humoral concept (hot-cold food) are no longer the practice of urban Malay women. Most women who take HRT expressed satisfaction with it as it reduced their menopause-related problems. They expressed strong beliefs in their doctor's ability to help them to gain control of their bodies. They dismissed the belief that HRT may have a potential association with cancer and if they were aware of this, they were prepared to take the risk. They are of the opinion that menopause must be managed by the experts like they treat childbirth experiences. Those who took HRT have negotiated menopausal treatment in a different social environment compared to their mothers who were very silent about their condition. It is difficult to know their mothers actually had symptoms because this was not discussed, whereas for many urban Malay women of today, they belief they need to exist within a 'modern' world which demands that they perform in the workplace and in the private spaces of the bedroom. Briefly, women who lost control over their bodies are more likely to comply with medical intervention not traditional practices or herbal remedies and therefore are likely to place faith in their doctor and the doctor's ability to deal with their menopausal symptoms.